Chemical Pulps for Writing and Printing Papers from Guatemala grass (Tripsacum luxum Nash) - Guha, S. R. D.; Pant, P. C.; Singh, S. P. (Indian Forester, 1966)
Laboratory experiments on the production of chemical pulps for writing and printing. Papers by Soda process from Guatemala grass (Tripsacum luxum Nash) are described. The average fibre length was 1.16 mm and the average fibre diameter was 0.010 mm. Easy bleaching pulps with satisfactory strength properties for production of writing and printing papers could be prepared under suitable conditions from this grass.